Improving supply chain performance through quality management in a global distribution environment. (21st February 2005) - Beresford, A.K.C.; Pettit, S.J.; Whittaker, W.
In the context of international logistics, benchmarking systems such as Quality Assurance Accreditation (QAA), Total Quality Management (TQM) and internal Composite Logistics Modelling (CLM) tools can be combined to maximise logistics efficiency. This paper assesses the contribution of TQM/CLM systems to performance enhancement in a global logistics environment by means of a survey of logistics companies and a case study of a global logistics service provider which uses both internal and external quality management systems and CLM techniques in order to provide optimal solutions for the global distribution of automotive components. It is shown that such techniques contribute positively to a company's internal efficiency and to its position in the market.